Association of SNP markers with height increment in two MPOB-Angola oil palm populations, Malaysia - Ong, Pei Wen (2012)
Low height increment is a desired trait in oil palm (Elaeis guineensis) breeding. Palms with low height increment have the advantage of facilitating fruit harvesting and extending the economic life of the oil palm. The natural oil palm germplasm collected from Angola has high genetic variation in height increment and therefore invaluable for oil palm improvement and breeding programmes. Single nucleotide polymorphism (SNP) based cleaved amplified polymorphic sequence (CAPS) marker assay is simple and reliable for SNP detection. This approach has widely been used in plant genetics and breeding. In this marker-trait association study, a total of 219 palms from two MPOB Angola oil palm germplasm populations namely AGO01 and AGO08, were successfully genotyped with nine informative SNP markers. These markers include three random SNPs and six candidate gene SNPs which were converted into CAPS marker. Molecular data revealed a high level of genetic diversity among the MPOBAngola populations when compared with the advanced breeding population. The dendrogram constructed did not group the oil palm according to the populations and families. The palms included in the study could have originated from other provinces due to human migration during the civil war in Angola. AMOVA analysis indicated the main contribution to the total genetic variation was due to variation within populations (99%) and remaining 1% was explained by variation between populations. The population structure analysis indicated K = 2 which suggested that the samples was made up of two main genetic groups. Association analysis between SNP markers and height increment was analyzed with four different models in TASSEL software. The incorporation of population structure and kinship correction factors into the association models had reduced the number of significant markers detected. Marker SNPG00006_FatI was found to be significantly associated with height increment trait for all the TASSEL models tested. The results from SAS analysis further supported the significant association of this marker (SNPG00006_FatI) with height increment. This indicated the potential application of SNPs in identifying molecular markers associated with height increment and other traits in oil palm.